Purchasing and supply management (PSM) competencies: Current and future requirements. Issue 5 (December 2019) - Bals, Lydia; Schulze, Heike; Kelly, Stephen; Stek, Klaas
Abstract: Purchasing & Supply Management (PSM) competencies are the individual-level foundations of organisational PSM performance. In light of recent developments in the workplace and the external environment, the question of what PSM competencies are needed now, as well as in the future, becomes one of increasing importance. Analysing qualitative data from 46 interviews from 16 companies, this paper identifies what current and future competencies are required by PSM professionals, categorizes PSM competencies according to the framework established by Tassabehji and Moorhouse (2008) and establishes how these competency requirements have changed over the last ten years. The most important current competencies required by PSM professionals are negotiation, communication and relationship management (e.g. 'Interpersonal communication'), strategy and analytics (e.g. 'Strategic thinking'), as well as professional knowledge requirements (e.g. 'Basic knowledge on PSM role & processes'). When looking at future requirements, competencies in the areas of sustainability and digitisation were identified as becoming increasingly important. Overall, 17 competencies in addition to those shown in Tassabehji and Moorhouse (2008) were identified. The most prominent new competency areas are related to digitisation (e.g. 'eProcurement Technology', 'Automation'), innovation (e.g. 'Innovative sourcing') and sustainability. The interviewees also identified 11 new competencies within the interpersonal skills cluster, most of them at the intersection between competencies and traits (e.g. 'Deal with Ambiguity', 'Curiosity', 'Passion'). Highlights: Based on a literature review, PSM professionals need both procurement specific and generic management competencies. Based on 46 interviews with 16 companies, both current and future competency requirements were empirically identified. 17 competencies in addition to the framework by Tassabehji and Moorhouse (2008) were identified as becoming important. The newly added competencies are most notably in the areas of digitisation, innovation and sustainability.